Strategi Keberhasilan Komunikasi Pemasaran Bank Digital dalam Membangun Kepercayaan Nasabah Generasi Milenial dan Gen Z - Yudhistira Wirya Saputra; Agatha Anggraeni Dewi; Rini Sudarmanti (Comit: Communication, Information and Technology Journal, 2026)
The rapid development of digital technology has transformed the banking industry through the emergence of digital banks that operate without physical branch offices. This condition creates communication challenges, particularly in building customer trust, as banking services are intangible and involve high perceived risk. Millennials and Generation Z have become the primary users of digital banking services due to their high level of digital literacy and reliance on mobile-based financial applications. This study aims to analyze the success strategies of digital marketing communication implemented by digital banks in building trust among Millennial and Generation Z customers. This research employs a descriptive qualitative approach with a case study method. Data were collected through content analysis of digital marketing communication materials published by digital banks on digital platforms, supported by in-depth interviews exploring the perceptions and subjectivity of Millennial and Generation Z customers. The analytical framework draws on the concept of digital marketing communication (Kotler & Keller, 2016) and the dimensions of trust in online services (Gefen et al., 2003). The findings indicate that digital bankls emphasize four main communication messages: transaction security, cost efficiency, service convenience, and institutional credibility, delivered consistently through social media, mobile applications, and official websites using persuasive narratives, visual communication, and customer testimonials. This study concludes that strategically managed digital marketing communication plays a significant role in reducing perceived risk and strengthening customer trust in digital banking services.